The role of non-governmental organizations in the mental health area - Zupančič, Vesna (Zdravstveno varstvo, 2016)
Introduction. The contributions' aim is highlighting the differences in understanding non governmental organizations' (NGOs) role in the mental health area within the public support network for patients with mental health problems from various viewpoints, in order to achieve progress in supporting patients with mental health problems in local communities. Methods. Qualitative data gathered as a part of a cross-sectional study of NGOs in the support network for patients with mental health problems in two Slovenian health regions (56 local communities), carried out in 2013 and 2014, were used. Qualitative analysis of interviews, focus groups and answers to an open survey question was performed. Results. There are differences in understanding NGOs' role in the support network for patients with mental health problems, which stem from the roles of stakeholders (local community officials, experts, care providers, and patients) within this system and their experience. Discussion and conclusion. The actual differences need to be addressed and overcome in order to provide integrated community care. The importance of knowing the current state of NGOs in their life cycle and the socio-chronological context of the local community support network is evident.
Keywords: collaboration; community approach; duševno zdravje; integrated care; local communities; lokalne skupnosti; mental health; mentalno zdravje; nevladne organizacije; non-governmental organizations